2002
DOI: 10.1071/pp01182
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of Chlamydomonas to changing carbon availability

Abstract: Aquatic organisms, including Chlamydomonas reinhardtii, are faced with a variable supply of dissolved inorganic carbon (Ci). Accordingly, C. reinhardtii has the ability to acclimate to the changing Ci supply through a variety of responses, including induction of a CO2 concentrating mechanism (CCM) when Ci is limiting. The CCM uses active Ci uptake to accumulate a high internal concentration of bicarbonate, which is dehydrated by a specific thylakoid carbonic anhydrase to supply CO2, the substrate used in photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 77 publications
(107 reference statements)
1
27
0
Order By: Relevance
“…Furthermore, Ci uptake is higher in chloroplasts isolated from low-than from high-CO 2 -grown cells (8). Genes involved in Ci uptake by Chlamydomonas are strongly induced when high-CO 2 -grown cells are transferred to low-CO 2 conditions (12,13,19,20). Mutants in which these genes were impaired required high CO 2 for growth.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Ci uptake is higher in chloroplasts isolated from low-than from high-CO 2 -grown cells (8). Genes involved in Ci uptake by Chlamydomonas are strongly induced when high-CO 2 -grown cells are transferred to low-CO 2 conditions (12,13,19,20). Mutants in which these genes were impaired required high CO 2 for growth.…”
mentioning
confidence: 99%
“…As opposed to CO 2 supply, there is far less information regarding the mechanism of HCO 3 Ϫ uptake in Chlamydomonas. Nevertheless, isolated chloroplasts of Chlamydomonas can accumulate HCO 3 Ϫ to levels higher than could be accounted for by passive diffusion (13). Furthermore, Ci uptake is higher in chloroplasts isolated from low-than from high-CO 2 -grown cells (8).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although initially identified as a probable Ci transport mutant, a recent study reported that the expression profiles of several CO 2 responsive genes in pmp1 differ from those in wild type and suggested that the Pmp1 gene product might regulate the expression of Ci transporter genes (14). Another recent observation regarding pmp1 is its unusual, air-dieing phenotype (15,16): it grows well in either high (5%) or very low (Ͻ200 ppm) CO 2 , but dies in low (air-level) CO 2 (350-450 ppm). This conspicuous phenotype distinguishes pmp1 from most other high CO 2 -requiring mutants and indicates the existence of multiple Ci transport systems in C. reinhardtii corresponding to multiple, CO 2 level-dependent acclimation states.…”
mentioning
confidence: 99%